KETERLIBATAN POLITIK GENERASI MUDA DI ERA DIGITAL: DINAMIKA, TANTANGAN, DAN PELUANG DALAM PENDEKATAN KUALITATIF - Sobali Suswandy; Muhammad Hendriyana; Rivaldi Saputra; Muhammad Abdul Fatah; Latif Latif; Bagya Fajar Sidik (Educatus, 2025)
Young people play a strategic role in promoting political participation and strengthening democracy in Indonesia. This study aims to examine the political engagement of young people in the digital era, focusing on the dynamics, challenges, and opportunities they face. Using a qualitative approach, data were collected through in-depth interviews and case studies involving informants from diverse social, educational, and geographical backgrounds. The findings reveal that the digital era has opened wider spaces for youth participation through various social media platforms and online communities. However, challenges remain, such as low political literacy, apathy toward the political system, and unequal access to technology and information. On the other hand, opportunities include easier mass mobilization, strengthened social networks, and increased political awareness through digital content. These findings suggest that optimizing the role of young people in politics requires inclusive political education strategies, equitable access to technology, and more open spaces for participation.